2004
DOI: 10.1177/135065010421800206
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of experimental observations of a single transverse ridge passing through an elastohydrodynamic lubrication point contact under rolling/sliding conditions

Abstract: Recent experimental observations by Fe lix-QuinÄ onez, Ehret and Summers (Trans. ASME, J. Tribology, 2003, 125, 252±259) for a single,¯at-top transverse ridge passing through an elastohydrodynamic lubrication (EHL) point contact under various slide±roll ratios have revealed some unexpected features. In particular, under sliding conditions the ridge was observed to sustain additional deformations in the high-pressure region of the contact and an entrapped amount of lubricant was seen to accompany the ridge dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In this article, the combined 2nd-order backward differential scheme is used to discretize the Couette flow on the right side of the Reynolds Eq. (20), whilst the 2nd-order central differential scheme is used to process the left side, the Poiseuille flows. At each mesh point, the values of / x , / y , and e are computed from the initial values of film thickness and pressure at current point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, the combined 2nd-order backward differential scheme is used to discretize the Couette flow on the right side of the Reynolds Eq. (20), whilst the 2nd-order central differential scheme is used to process the left side, the Poiseuille flows. At each mesh point, the values of / x , / y , and e are computed from the initial values of film thickness and pressure at current point.…”
Section: Methodsmentioning
confidence: 99%
“…The only closed form of the two-dimensional generalized Newtonian Reynolds equation was presented by Greenwood [17] for the well-known but restrictive Rabinowitsch model. Numerical simulations usually use a sinh-law for the sliding case and the Newtonian assumption for pure rolling [18][19][20][21]. As shear thinning is ignored, film thickness reduction cannot occur under the pure rolling condition in these simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the effects of a surface feature, however, an important difference is observed on the film fluctuation here in that a lubricant accumulation appears to take place behind the location of the inclusion rather than in front of it, as it is found in the case of a surface ridge. 32,33 This result may be attributed to the slope of the displacements caused by the inclusion having a sign opposite to the slope of the displacements introduced by a surface ridge. As expected for pure rolling conditions where the lubricant and the bounding solids move at the same speed, both the pressure and film fluctuations appear at the same x-axis location than the inclusion.…”
Section: Contact Conditions Lubricant and Materials Parametersmentioning
confidence: 99%
“…Glovnea et al (2003) and Armando et al (2003) investigated experimentally, using optical interferometry technique, the behavior of a single transverse ridge in a circular elastohydrodynamic contact. Felix-Quinonez et al (2004) investigated numerically and experimentally the behavior of passage of a single flat-top transverse ridge through an elastohydrodynamic point contact under rolling/sliding conditions. They found that the geometrical characteristics of the ridge play an important role in the formation of lubricant film thickness.…”
Section: Introductionmentioning
confidence: 99%